Front Cover: A theoretical‐experimental methodology for assessing the sensitivity of biomedical spectral imaging platforms, assays, and analysis methods (J. Biophotonics 1/2018). Issue 1 (17th January 2018) - Leavesley, Silas J.; Sweat, Brenner; Abbott, Caitlyn; Favreau, Peter; Rich, Thomas C.
Abstract : A hyperspectral image data cube acquired from HEK‐293 cells labeled with cytoplasmic and nuclear stains: Calcein Green and NucBlu. The top view (XY plane) displays three spectrally unmixed channels for cellular autofluorescence (red), Calcein Green (green), and NucBlue (blue). The Z axis shows spectral information, from low to high wavelength. The article by Leavesley and colleagues describes an approach for calculating the sensitivity of spectral imaging assays for detecting a fluorescence signature within a mix of other signatures or autofluorescence. Further details can be found in the article by Silas J. Leavesley et al. (e201600227 ). Abstract : A hyperspectral image data cube acquired from HEK‐293 cells labeled with cytoplasmic and nuclear stains: Calcein Green and NucBlu. The top view (XY plane) displays three spectrally unmixed channels for cellular autofluorescence (red), Calcein Green (green), and NucBlue (blue). The Z axis shows spectral information, from low to high wavelength. The article by Leavesley and colleagues describes an approach for calculating the sensitivity of spectral imaging assays for detecting a fluorescence signature within a mix of other signatures or autofluorescence. Further details can be found in the article by Silas J. Leavesley et al. (e201600227 ).